The nutrient composition and in vitro ruminal degradability of selected local plants used as goat feed in Malaysia - Abdul Ghani, Ahmad Afifi; Shahudin, Muhammad Syafiq; Rashid, Muhammad Azrolharith; A. R., Haizan; Saad, Mohd Zamri; Abu Bakar @ Zakaria, Md Zuki; Haron, Abd Wahid; Kasim, Azhar; Salisi, Mohd Shahrom; Goh, Yong Meng; Yusoff, Rosnina; Abu Hassim, Hasliza (Veterinary Association Malaysia, 2017)
A comparative study of nutrient composition and in vitro ruminal degradability of selected local plants, Macaranga sp. and Mallotus sp. was carried out and Napier grass (Pennisetum purpureum) was used as control. The results obtained from proximate analysis revealed that there were significant difference (P<0.05) of all nutrient composition for each local plant species against Napier grass. Dry matter content in Macaranga sp., Mallotus sp. and Napier grass were 50.92%, 45.41% and 13.04%, respectively. The crude protein content in Macaranga sp., Mallotus sp. and Napier grass were 7.18%, 6.78% and 3.88%, respectively. Mallotus sp. has the highest crude fat content (5.22%) followed by Macaranga sp. (4.85%) and Napier grass (2.84%). Crude fibre content in Napier grass, Mallotus sp. and Macaranga sp. were 25.38%, 15.47% and 12.00%, respectively. For the in vitro ruminal degradability, total gas produced by Napier grass, Macaranga sp. and Mallotus sp. were 31.00 ml, 28.67 ml and 23.33 ml, respectively. Acetic acid production in Mallotus sp., Napier grass and Macaranga sp. were 733.49 mM/ml, 605.61 mM/ml and 599.85 mM/ml, respectively. Propionic acid production was highest in Mallotus sp. (28.61 mM/ml) followed by Napier grass (24.45 mM/ml) and Macaranga sp. (24.23 mM/ml). As for butyric acid production, Napier grass showed the highest value (11.26 mM/ml), followed by Macaranga sp. (11.19 mM/ml) and Mallotus sp. (10.36 mM/ml). However, there was no significant difference shown in acetic, propionic and butyricacids production. Thus, based on the nutrient composition and in vitro ruminal degradability results, it shows that these local plants could be used as an alternative feed source for goats.